The politics of environmental control in northeastern Tanzania, 1840-1940 - Giblin, James Leonard (Ethnohistory series (Philadelphia, Pa.), 1992)
A historical study of the relationship between political and environmental change in Tanzania's northeastern lowlands, an impoverished region that has been afflicted by severe food shortages throughout the twentieth century.